THE MATURITY OF RISK MANAGEMENT IN INDONESIAN ISLAMIC UNIVERSITIES - Marliyah, Marliyah; Dharma, Budi; Syarbaini, Ahmad (Faculty of Economic and Business, University of Pasundan, 2023)
The study aims to measure, investigate, and examine how Islamic Universities integrating Islamic transdisciplinary and risk management based on ISO 31000:2018 to their good university governance. This study was conducted in 2022, based on a content analysis approach to measure the maturity level of risk management. Researchers develop maturity index level suitable in higher education organization based on ISO 31000:2018 criteria that develop by IRMAPA. The analysis covers both quantitative and qualitative data that had been hand collected from number of Indonesian Islamic Universities. This study found that average maturity level of risk management in some of Indonesian Islamic Higher Education is risk aware where it is the 2nd level (the highest level is 5th). Researchers found that determining risk context was the most difficult stage to define. Findings can attract the attention, from a regulatory perspective.